PARTNER SCHOOLS EVALUATION OF PRE-SERVICE TEACHERS PERFORMANCE DURING FIELD PRACTICE: A CASE STUDY FROM FKIP UMMY SOLOK - Hana Adhia; Risza Dwiputri; Helvita Roza; Ikhwan; Redo Andi Marta; Roza Zaimil (Universitas Mahaputra Muhammad Yamin, 2026)
This study examines the performance evaluation of Field Practice (PLK) students from the Faculty of Teacher Training and Education (FKIP) UMMY Solok in 2025 based on assessments from partner schools. The research employed a descriptive quantitative method, collecting data through structured questionnaires distributed to supervising teachers at partner schools. Six key competency areas were assessed: professional ethics, communication skills, technology integration, teamwork and collegial collaboration, self-development and reflective practice, and teaching competence. The results indicate that PLK students demonstrated strong performance across all evaluated dimensions, with 100% of respondents rating teamwork and collegial collaboration, self-development and reflective practice, and teaching competence as